Investigating the Types of Value and Cost of Green Brands: Proposition of a Conceptual Framework - Papista, Erifili; Krystallis, Athanasios (2013)
This conceptual article applies the customer value (CV) concept in the context of green marketing aiming to provide insights on the factors that motivate and/or hinder the development of consumer–green brand relationships. The article draws upon existing literature on the streams of CV, relationship marketing and environmental behaviour and synthesises relevant findings to propose an integrated conceptual framework entailing all identified types of value and cost, psychographic characteristics, as well as dimensions of relationship quality (RQ) and loyalty. Furthermore, it addresses existing questions on the links among constructs and proposes several relationships that may lead to a better understanding of consumer behaviour towards green brands. Through the here-proposed conceptual model, the article initiates the process of empirically examining the consumer adoption of and relationship development with green brands. The CV framework adopted here may provide practitioners with knowledge on the value and sacrifice factors, as well as the dimensions of RQ that are the most important in targeting green consumers and designing relationship marketing strategies. The article also fulfils an identified gap in the literature, as it is the first that brings together and applies research findings from CV and relationship marketing fields in the green marketing context and proposes an integrated approach to understanding consumer–green brands relationships.
Keywords: Loyalty; Relationship quality; Cost; Customer value; Green brands